A Polyimide Nanolayer as a Metal‐Free and Durable Organic Electrode Toward Highly Efficient Oxygen Evolution. Issue 38 (27th August 2018) - Lin, Yun‐Xiao; Feng, Wei‐Jie; Zhang, Jun‐Jun; Xue, Zhong‐Hua; Zhao, Tian‐Jian; Su, Hui; Hirano, Shin‐Ichi; Li, Xin‐Hao; Chen, Jie‐Sheng
Abstract: The exploitation of metal‐free organic polymers as electrodes for water splitting reactions is limited by their presumably low activity and poor stability, especially for the oxygen evolution reaction (OER) under more critical conditions. Now, the thickness of a cheap and robust polymer, poly( p ‐phenylene pyromellitimide) (PPPI) was rationally engineered by an in situ polymerization method to make the metal‐free polymer available for the first time as flexible, tailorable, efficient, and ultra‐stable electrodes for water oxidation over a wide pH range. The PPPI electrode with an optimized thickness of about 200 nm provided a current density of 32.8 mA cm −2 at an overpotential of 510 mV in 0.1 mol L −1 KOH, which is even higher than that (31.5 mA cm −2 ) of commercial IrO2 OER catalyst. The PPPI electrodes are scalable and stable, maintaining 92 % of its activity after a 48‐h chronoamperometric stability test. Abstract : A polymer electrode composed of nanoscale and metal‐free poly( p ‐phenylene pyromellitimide) films on carbon cloth can act as flexible, tailorable, efficient, and ultra‐stable electrodes for water oxidation over a wide pH range. The electrode (optimized thickness ca. 200 nm) provided a current density of 32.8 mA cm −2 at an overpotential of 510 mV in 0.1 mol L −1 KOH (commercial IrO2 OER catalyst: 31.5 mA cm −2 ).